Flow cytometric analysis from fish samples stored at low, ultra-low and cryogenic temperatures - Yasui, George Shigueki; Bertolini, Rafaela Manchin [UNESP]; Suarez-Lopez, Lucia [UNESP]; Xavier, Pedro Porfirio; Monzani, Paulo Sergio; Nascimento, Nivaldo Ferreira do; Castilho, Antonio Leao [UNESP]; Okada Nakaghi, Laura Satiko [UNESP]; Alves dos Santos, Silvio Carlos; Senhorini, Jose Augusto (Elsevier B.V., 2020)
Flow cytometry is a valuable tool in biomedical and animal sciences. However, equipment used for such analysis presents limitations at field conditions, suggesting then preservation procedures for future analysis at laboratory conditions. In this study, freezing at low (-20 degrees C), ultra-low (-80 degrees C) and cryogenic temperatures (-196 degrees C, i.e. liquid nitrogen) were used as preservation procedures of fish tissue. Samples were maintained in 0.9% NaCl or lysing solution, and stored at the temperatures above for 0 (fresh control), 60, 120 and 180 days of storage. After storage, the samples were thawed and proceeded to flow cytometric analysis. Storage at low temperatures (-20 degrees C), both in lysing and 0.9% NaCl, exhibited poor results when analyzed after 60, 120 and 180 days, showing noisy peaks, deviation in the DNA content and absence of peaks. Ultralow (-80 degrees C) and cryogenic (-196 degrees C) temperatures, both in lysing solution and 0.9% NaCl, showed good results and high quality of histograms. Both storage procedures gave similar histograms and DNA content in comparison with control group (fresh) even after 60, 120 and 180 days of storage, exhibiting the main peak at 2C content from diploid cells and a secondary peak at 4C derived from dividing cells. In conclusion, samples may be stored for 180 days at -80 degrees C and -196 degrees C in both, 0.9% NaCl or lysing solution. As cryogenic temperatures in liquid nitrogen permits indefinite storage, this procedure should be used for long-term preservation.
Keywords: Cell cycle; DNA quantity; Fish; Ploidy; Storage